تأثير الإجهاد الملحي في بعض المعايير الفيزيولوجية والشكلية عند بعض أصناف الذرة الصفراء (Zea mays L.) (Latakia University Journal -Biological Sciences Series, 2019)
هدفت الدراسة إلى تقويم تأثير أربعة مستويات ملحية من ماء البحر (شاهـد ، 1 ، 2 ، و3 ضغط جوي)، في بعض الخصائص الشكلية (طول الجذير وغمد الريشة)،  وبعض الصفات الفيزيولوجية عند أربعة أصناف من الذرة الصفراء المزروعة في سورية (غوطة 1، غوطة 82، الباسل 1 والباسل 2 ). نُفذ البحث في الظروف المخبرية ، في أصص يحتوي كل منهـا 3 كغ تربة رملية، وبمعدل ثلاث مكررات لكل معاملة ، باستخدام تصميم القطع المنشقة لأكثر من مرة ، واستمر ستة أسابيع. بينت نتائج البحث أن زيادة الجهد الحلولي أثرت سلباً في نمو البادرات ، وفي الوزن الجاف للمجموع الخضري، وفي المساحة الورقية، وفي محتوى الورقة من الكلوروفيل، وفي المحتوى المائي النسبي في الورقة،  فضلاً عن أنهـا زادت من كمية الصوديوم وقللت من كمية البوتاسيوم مما أدى إلى ازدياد نسبة شوارد الصوديوم إلى البوتاسيوم في نسيج الورقة. وجدت علاقة ارتباط سلبية بين تركيز الصوديوم في الورقة وبقية المعايير المدروسة وبخاصة كمية المادة الجافة، كما أظهر حساب معامل التحديد أن نسبة  Na+/K+ أكثر مساهمة في تحديد المادة الجافة من المعايير الأخرى المدروسة. أبدى الصنفان غوطة 1 والباسل 2  تحملاً أكثر لزيادة الجهد الحلولي. Most crop plants suffer after exposure to saline conditions and showed decline in growth. The objective of this study was to assess and compare  four Zea mays cultivars Syrian (Gota 1, Gota 82, Albassel 1 and Albassel 2 ), under the effect of four  osmotic pressure levels (control, 1, 2, and 3 Atmo.P ). The experiment was conducted in the laboratory in pots contain sandy soil, with three replicates in split- split plot design. Three days after seedlings establishment, salinity was raised to required level  and was maintained throughout the experiment. Plants were grown for sex weeks. Data were subjected to statistical analysis of variance according to Anova test. L.S.D. at the 5% level of significance was used to compare among means. The results showed that  increasing osmotic pressure of irrigation water decreased the studied seedling characteristics (radicl length and coleoptile length), shoot dry weight, leaf area, relative water content and chlorophyll content in the leaf tissue. The salt stress reduced the uptake of  K+, but increased the uptake of  Na+ ; this led to increase  Na+/K+ ratio in the leaf . The sodium concentration in the leaf tissue was correlated negatively with all physiological and morphological parameters investigated. Na+/K+ ratio in the leaf largely determined the dry weight, but relative water content in the leaf had little effect on it. Analysis of variance showed significant cultivar x osmotic pressure level interaction. This indicates that cultivars responded differently across osmotic potential levels. In the light of the findings of this study, it could be said that the Gota 1 and Albassel 2 cultivars are more salt tolerant.